When is human capital a valuable resource? The performance effects of Ivy league selection among celebrated CEOs - Miller, Danny; Xu, Xiaowei; Mehrotra, Vikas (Strategic Management Journal, 2015)
We investigate whether and when highly trained human capital constitutes a rent‐sustaining resource. Our study of 444 CEOs celebrated on the covers of major U.S. business magazines found an advantage accruing to graduates of selective universities. Such CEOs led firms with higher and more sustained market valuations. The advantage was strongest for undergraduate programs as these related to the kinds of talent demanded of a CEO . The advantage also was greatest in smaller firms where CEO discretion might be highest and for younger CEOs who may benefit most from college and are less able to appropriate rents. Finally, the advantage accrued to graduates of more recent years, when selective schools had become less socially elitist and increasingly meritocratic, thus favoring human versus social capital . Copyright © 2014 John Wiley & Sons, Ltd.